Do distribution and expansion of exotic invasive Asteraceae plants relate to leaf construction cost in a man-made wetland?. (February 2021) - Li, F.L.; Zhong, L.; Wen, W.; Tian, T.T.; Li, H.C.; Cheung, S.G.; Wong, Y.S.; Shin, P.K.S.; Zhou, H.C.; Tam, N.F.Y.; Song, X.
Abstract: Exotic species especially Asteraceae plants severely invade wetlands in Shenzhen Bay, an important part of the coast wetland in Guangdong-Hong Kong-Macau Bay Area, China. However, the reasons causing their expansion are unclear. The leaf traits and expansion indices of six invasive Asteraceae plants from the Overseas Chinese Town (OCT) wetland were studied and the results showed that nearly 45% of the total plant species (31 out of 69 species) in the OCT wetland, belonging to 15 families and 27 genera, were exotic invasive species. The expansion indices of six Asteraceae species negatively correlated with their leaf construction cost based on mass (CCM), caloric values and carbon concentration, but their relations with ash content were positive. Multiple linear regression analysis revealed that CCM was the most important factor affecting the expansion of an exotic species, indicating CCM may be an important reason causing the expansion of exotic species in coastal wetlands.